Trail and Error!

Algebra Level pending

For a function f ( x ) f(x) ,

f ( 1 ) f ( 1 ) = 6 f ( 2 ) f ( 2 ) = 3 f ( 3 ) f ( 3 ) = 2 f ( 6 ) f ( 6 ) = 1 f(1) - f(-1) = 6\\f(2) - f(-2) = 3\\f(3) - f(-3) = 2\\f(6) - f(-6) = 1

If the above information holds true, and f ( x ) f ( x ) f(x) - f(-x) follows same pattern for all values of x x , find the value of f ( 12 ) f ( 12 ) f(12) - f(-12)

9 1 2 \frac{1}{2} 6 5 \frac{6}{5} 6 6 2 2 3 7 \frac{3}{7} 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Viki Zeta
May 30, 2016

Seeing all those given information,

f ( 1 ) f ( 1 ) = 6 f ( 2 ) f ( 2 ) = 3 f ( 3 ) f ( 3 ) = 2 f ( 6 ) f ( 6 ) = 1 f(1) - f(-1) = 6\\f(2) - f(-2) = 3\\f(3) - f(-3) = 2\\f(6) - f(-6) = 1

It's clear that,

f ( x ) f ( x ) = 6 x f(x) - f(-x) = \frac{6}{x}

So, f ( 12 ) f ( 12 ) = 6 12 = 1 2 f(12) - f(-12) = \frac{6}{12} = \frac{1}{2}

Santo Chandra
May 29, 2016

It's geometric series

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...